Powdery Mildew of Strawberries - Natalia A. Peres; James C. Mertely (EDIS)
Powdery mildew occurs in most areas of the world where strawberries are grown, infecting leaves, flowers, and fruit. Infected transplants are normally the primary source of inoculum for fruiting fields in Florida, but even disease-free fields can become infected by conidia blown in from neighboring fields. Fields with susceptible cultivars should be surveyed regularly for powdery mildew, especially early in the season. Usually, controlling foliar infection helps to prevent fruit infection. This 4-page fact sheet was written by N. A. Peres and J. C. Mertely, and published by the UF Department of Plant Pathology, May 2013.